A REVERSE PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY-PHOTO DIODE ARRAY ESTIMATION OF PROBENECID AND SULOPENEM ETZADROXIL IN BULK AND PHARMACEUTICAL DOSAGE FORM AND CHARACTERIZATION OF DEGRADANTS BY USING LIQUID CHROMATOGRAPHY MASS SPECTROMETRY - RAJU, M. DAVID; PALIVELA, PRAVEEN KUMAR; RAYINUTHALA, YESUPADAMU (International Journal of Applied Pharmaceutics, 2026)
Objective: This study presents a valid and dependable "Reverse Phase High-Performance Liquid Chromatography (RP-HPLC)" technique for the simultaneous quantification of sulopenem etzadroxil and probenecid in their pharmaceutical dose form, which indicates stability. Methods: Probenecid and sulopenem etzadroxil were isolated by using an isocratic elution technique with a phenyl column (250 mm x 4.6 mm, 5μm) and a mobile phase consisting of acetonitrile and triethyl amine at a pH of 2.5, which was adjusted with a 0.1% formic acid buffer in a 60:40 ratio, and a flow rate of 1.0 ml/min, respectively. Sulopenem etzadroxil and probenecid were quantified using a 271 nm detection wavelength. Results: At retention durations of 2.631 and 4.048 min, respectively, the peaks for probenecid and sulopenem etzadroxil were eluted with fine resolution. Both probenecid and sulopenem etzadroxil showed linear calibration curves with regression coefficients of 0.99998 and 0.99975 in the concentration range of 50-300 μg/ml respectively. Resolution of probenecid and sulopenem etzadroxil from its degradation-based chemicals demonstrated the sensitivity, precision, robustness, accuracy, and specificity of the proposed high-performance liquid chromatography method and also indicated stability. The degradation agents were identified by the use of LCMS in the research involving forced degradation. Conclusion: The pharmaceutical dosage forms of probenecid and sulopenem etzadroxil were evaluated using the well-established high-performance liquid chromatography method, and the findings seemed adequate.